Removal of copper from solution using moss - Lee, C.K.; Low, K.S. (Taylor & Francis Group, 1989)
Studies were carried out to assess the capability of a moss, Calymperes delessertii Besch, to remove copper from solution. Both batch and column experiments were performed, taking into account such parameters as pH, sorbent dosage, copper concentration, presence of other metal ions, temperature, contact time, column height and flow'rate. The results show that the moss is an efficient sorbent for copper removal and the mechanism is mainly an ion‐exchange process.